The Strengths-Based Performance Profile (SBPP): A Method for Strengths-Spotting and Application in Single-Session Consultations with Athletes. Issue 3 (3rd July 2022) - Castillo, Elmer A.; Bird, Matthew D.
Abstract: The performance profile technique is a standard, theory-driven sport and performance psychology intervention for enhancing various psychological outcomes within athletes and teams. Despite the popularity of the technique, current literature and practices are focused almost exclusively on performance profiling for deficiency driven purposes and addressing identified areas for improvement. The purpose of this paper is to introduce a radical adaptation of the performance profile technique anchored in positive psychology (i.e., strengths-based approaches and broaden-and-build theory of positive emotions) and solution-focused principles to build mental readiness in single-session contexts. The conceptual, theoretical, and empirical rationale, overview, benefits, and applied considerations of the strengths-based performance profile (SBPP) are presented herein to propose a novel strengths-focused application of the performance profiling procedure. To conclude, we discuss how the SBPP technique can be used to help athletes, coaches, and sport psychology professionals better understand, assess, and capitalize on existing strengths in preparation for upcoming performances.